THE RELATIONSHIP BETWEEN STUDENTS’ MOTIVATION AND THEIR LISTENING ACHIEVEMENT AT ENGLISH LANGUAGE EDUCATION STUDY PROGRAM OF KHAIRUN UNIVERSITY - Asrul Asrul (Universitas Khairun, 2018)
The aims of this research is to find out whether or not there is a significant relationship between students’ motivation and their listening achievement. Quantitative method was applied in this research with correlation design. The population of the study was the second semester students of English Language Education Study Program of Khairun University academic year 2016/2017. The sample of this research consisted of 30 students and they were selected by using convenience sampling technique. The data were collected through questionnaire and listening scores. The result of this research shows that r is -0.28. This relationship is small (low) because r value is between 0.10 and 0.29. The result could be classified that the relationship between the two variables is not significant because the r is small (low). It means that the alternative hypothesis (Ha) stating that there is a significant relationship between students’ motivation and their listening achievement is rejected and null hypothesis (Ho) stating that there is no significant relationship between students’ motivation and their listening achievement is accepted. This suggests that students with high motivation do not guarantee high achievement in learning listening comprehension.Keyword : Relationship, motivation, listening achievement